The visual induction of music through projection mapping - Fantinati, Giovani Veras; Corrêa, Antenor Ferreira (DAT Journal, 2024)
In this article, we consider the technique of projecting images onto non-flat surfaces called projection mapping. Although pioneering in 1969, this technique only recently acquired better defined artistic contours, thus giving new meaning to spaces and forms of interactions with other artistic languages. In view of this, we propose the following question: how the projection mapping technique has been approached in academic literature in Brazil? Based on this question, the article was structured in three moments: bibliographic survey, synthesis of the bibliographic material collected, and analysis of a work that uses the projection mapping technique. This analysis aimed to understand the relationship between image and sound.